Collaborative Design and Live Interaction with Parametric Models using UbiMash - Salim, Flora Dilys; Mulder, Hugo; Jaworski, Przemyslaw; Ransom, James Willems; Cutellic, Pierre; Iseki, Takehiko; Di Leo, Stefan; Kom, Yelta (SAGE PUBLICATIONS LTD, 2010)
Due to the complexity of parametric modeling, it has been the task of only a handful of experts in the design team to develop, build and modify parametric models. The complexity of parametric models increases exponentially with the number of design aspects it incorporates. The ambiguity of parametric models towards the modeled design intent explains that modifying the model is often isolated as an individual exercise. Developments in physical and ubiquitous computing, however, allow for collaboration and interaction with parametric models in other ways. Communication, coordination, and interaction between parametric models and the physical and social environment are the context of this paper. The paper describes some of the projects that were outcomes of the SmartGeometry 2010 workshops. These projects are dealing with mass collaboration using Twitter, tangible interfaces, parametric design and construction coordination and geometrical interpretation of datasets.
Keywords: parametric design; interactive parametric model; design collaboration; physical computing; ambient computing; form fostering; UbiMash; SmartGeometry; Architecture